The novel late Na+ current inhibitor, GS‐6615 (eleclazine) and its anti‐arrhythmic effects in rabbit isolated heart preparations. (14th September 2016) - Rajamani, Sridharan; Liu, Gongxin; El‐Bizri, Nesrine; Guo, Donglin; Li, Cindy; Chen, Xiao‐Liang; Kahlig, Kristopher M; Mollova, Nevena; Elzein, Elfatih; Zablocki, Jeff; Belardinelli, Luiz
Abstract : Background and Purpose: Enhanced late Na + current (late INa ) in the myocardium is pro‐arrhythmic. Inhibition of this current is a promising strategy to stabilize ventricular repolarization and suppress arrhythmias. Here, we describe GS‐6615, a selective inhibitor of late INa, already in clinical development for the treatment of long QT syndrome 3 (LQT3). Experimental Approach: The effects of GS‐6615 to inhibit late INa, versus other ion currents to shorten the ventricular action potential duration (APD), monophasic APD (MAPD) and QT interval, and decrease to the incidence of ventricular arrhythmias was determined in rabbit cardiac preparations. To mimic the electrical phenotype of LQT3, late INa was increased using the sea anemone toxin (ATX‐II). Key Results: GS‐6615 inhibited ATX‐II enhanced late INa in ventricular myocytes (IC50 = 0.7 μM), shortened the ATX‐II induced prolongation of APD, MAPD, QT interval, and decreased spatiotemporal dispersion of repolarization and ventricular arrhythmias. Inhibition by GS‐6615 of ATX‐II enhanced late INa was strongly correlated with shortening of myocyte APD and isolated heart MAPD (R 2 = 0.94 and 0.98 respectively). In contrast to flecainide, GS‐6615 had the minimal effects on peak INa . GS‐6615 did not decrease the maximal upstroke velocity of the action potential (Vmax) nor widen QRS intervals. Conclusions and Implications: GS‐6615 was a selective inhibitor of late INa, stabilizes the ventricular repolarization and suppresses arrhythmias in a model of LQT3. The concentrations at which the electrophysiological effects of GS‐6615 were observed are comparable to plasma levels associated with QTc shortening in patients with LQT3, indicating that these effects are clinically relevant.